Surface Modification, Characterization and Photocatalytic Performance of Nano-Sized Titania Modified with Silver and Bentonite Clay - Neetu Divya; Ajay Bansal; Asim K. Jana (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2009)
In many textile industries dyes are used as coloring agents. Advanced oxidation processes are used for degrading or removing color from dye baths. Catalysts play a key role in these industries for the treatment of water. Solid catalysts are usually composed of metals that form supports onto the surface and create metal particles with high surface areas. TiO2 composites containing transition metal ions (silver) and/or bentonite clay were prepared. Photocatalytic efficiencies have been investigated for the degradation of Orange G an azo dye. Various analytical techniques were used to characterize the surface properties of nano-sized titania modified using silver and/or bentonite clay. Scanning electron microscopy (SEM), Transmission electron microscopy (TEM), X-ray diffraction (XRD) and FTIR analyses showed that TiO2 (10 ± 2 nm) and Ag (2 to 3 nm) particles were supported on the surface of the bentonite clay and the size was in the range of 100 ± 2 nm. The modified catalysts P-25 TiO2/Bentonite/Ag and P-25 TiO2/Ag were found to be very active for the photocatalytic decomposition of Orange G. The percent decolorization in 60 min was 98% with both P-25 TiO2/Ag and P-25 TiO2/Bentonite/Ag modified catalysts. Whereas mineralization achieved in 9 hr were 68% and 71% with P-25 TiO2/Bentonite/Ag and P-25 TiO2/Ag catalyst respectively. © 2009 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)